OBOWIĄZKI PRZEDSIĘBIORCY I KARNOPRAWNE KONSEKWENCJE ICH ZANIECHANIA - Sachajko, Marek (Wydział Prawa i Administracji UAM, 2002)
The Business Activity Law Act regulates such areas as the obligations involved in undertaking and conducting business activities by entrepreneurs. These obligations have a variety of legal characters and they serve a number of different functions. They refer, for instance, to the conditions of conducting a business activity, possession of appropriate professional qualifications to conduct specific types of business activity, registering an entrepreneur and traded products as well as requirements regarding payment transactions in trade with existing entrepreneurs on the market. Violation of one’s obligations entails a number of different legal consequences other than administrative, such as penal liability for violation. However, in order to consider a breach of one>s administrative duties to be a violation of the law, each of the two conditions must be met: the committed act must be unlawful (prohibited by an act under the threat of a penalty) and injurious to the public. A violation of an order does not entail liability for a violation of the law i f the act is not injurious to the public. Criminal provisions are regulated by chapter 9 of the act. However, because of the textual character of any criminal norm, which is to refer to other legislative texts, the definition of a violation is determined not only by the Business Activity Law Act but also other administrative legal norms referred to by the Act. There is a large number of administrative and legal norms regulated in separate acts and binding for an entrepreneur in the course o f conducting a business activity. This article only deals with the criminal consequences of neglecting these obligations. It is a duty of eligible administrative bodies to oversee the discharge of these obligations imposed upon entrepreneurs. If a violation (as defined in chapter 9 of the Act) is disclosed, then eligible administrative bodies have the powers of a public prosecutor, providing that they have disclosed the violation and applied for the punishment in the scope of their competences. The court competent to consider violation cases is the regional court, which applies the procedure proper for violation cases. According to the principle o f criminal law subsidiarity, criminal measures only serve a supplementary function to the administrative means of administrative duty obligations imposed upon entrepreneurs. In administrative law enforcement the main role is played by administrative law instruments including administrative execution means. These execution means are the most apt for the character of the activities that are taken by the administrative bodies and that aim at implementing the norms of material administrative law on undertaking and conducting business activity.
ENTREPRENEUR’S OBLIGATIONS AND THE CONSEQUENCES OF THEIR NEGLIGENCE UNDER CRIMINAL LAW